Deep Learning-Based Recognition of Different Thyroid Cancer Categories Using Whole Frozen-Slide Images - Zhu, Xinyi; Chen, Cancan; Guo, Qiang; Ma, Jianhui; Sun, Fenglong; Lu, Haizhen (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Introduction: The pathological rare category of thyroid is a type of lesion with a low incidence rate and is easily misdiagnosed in clinical practice, which directly affects a patient's treatment decision. However, the recognition of rare, benign, and malignant categories of thyroid using the deep learning method and recommended the rare to pathologists is not adequately investigated. Methods: We present an empirical decision tree based on the binary classification results of the patch-based UNet model to predict rare categories and recommend annotated lesion areas to be re-reviewed by pathologists. Results: Applying this framework to 1,374 whole-slide images (WSIs) of frozen sections from thyroid lesions, we obtained an area under a curve of 0.946 and 0.986 for the test datasets with and without WSIs, respectively, of rare types. However, the recognition error rate for the rare categories was significantly higher than that for the benign and malignant categories (p < 0.00001). For rare WSIs, the addition of the empirical decision tree obtained a recall rate and precision of 0.882 and 0.498, respectively; the rare types (only 33.4% of all WSIs) were further recommended to be re-reviewed by pathologists. Additionally, we demonstrated that the performance of our framework was comparable to that of pathologists in clinical practice for the predicted benign and malignant sections. Conclusion: Our study provides a baseline for the recommendation of the uncertain predicted rare category to pathologists, offering potential feasibility for the improvement of pathologists’ work effencicy.